1999
DOI: 10.1074/jbc.274.52.37435
|View full text |Cite
|
Sign up to set email alerts
|

N-Myristoylation and βγ Play Roles beyond Anchorage in the Palmitoylation of the G Protein αoSubunit

Abstract: Many of the ␣ subunits of heterotrimeric GTP-binding regulatory proteins (G proteins) are palmitoylated, a modification proposed to play a key role in the stable anchorage of the subunits to the plasma membrane. Palmitoylation of ␣ subunits from the G i family is preceded by N-myristoylation, which alone or together with ␤␥ probably supports a reversible interaction of the ␣ subunit with membrane as a prerequisite to the eventual incorporation of palmitate. Previous studies have not addressed, however, the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…The function of the ␤␥ complex in helping to localize the ␣ subunit to the PM has been demonstrated recently (6,33,37), but little is known about the localization of ␤␥ itself except that it is considered to be anchored at the PM by prenylation (38). Here we have demonstrated that ␤␥ localizes to the PM very poorly when overexpressed in HEK293 cells.…”
Section: Discussionmentioning
confidence: 80%
“…The function of the ␤␥ complex in helping to localize the ␣ subunit to the PM has been demonstrated recently (6,33,37), but little is known about the localization of ␤␥ itself except that it is considered to be anchored at the PM by prenylation (38). Here we have demonstrated that ␤␥ localizes to the PM very poorly when overexpressed in HEK293 cells.…”
Section: Discussionmentioning
confidence: 80%
“…G s ␣ is then repalmitoylated and binds again to ␤␥ (72). Studies of palmitoylation of G o ␣ and G z ␣ have shown a similar relationship between palmitate modification and activation state (73). Palmitoylation of G z ␣ inhibits its interaction with the G z GAP and other RGS proteins that stimulate hydrolysis of G z ␣-bound GTP (74).…”
Section: Connection Between Ha-ras Palmitoylation and Activation-mentioning
confidence: 99%
“…The ability of the ␤ subunit to influence targeting of the ␥ subunit was surprising, because the ␤ subunit is not known to have a membrane-targeting signal, such as the prenyl group on the ␥ subunit (Wedegaertner et al, 1995). Because ␣ o was reported recently to target ␤ 5 RGS7 to the plasma membrane (Takida et al, 2005), we hypothesized that plasma membrane targeting of ␤ 5 ␥ 2 also might require ␣ o , which is not expressed in HEK-293 cells (Wang et al, 1999b). Indeed, we found that coexpressed ␣ o did target both Cer-C-␤ 5 Cer-N-␥ 2 and Cer-C-␤ 5 Cer-N-RGS7 to the plasma membrane (Fig.…”
Section: Downloaded Frommentioning
confidence: 99%